Studies on the Preparation and Thermal Stability of SiO2 Aerogels Doped with Fibrous Bructite and TiO2 Opacifier - Zhang, Weina; Lu, Jilong; Zhu, Jianwei; Cui, Wenbo (Asian Journal of Chemistry, 2012)
The reinforced silica aerogel and composite silica aerogel doped with fibrous bructite and titanium dioxide opacifier had been prepared by sol-gel method and supercritical drying technique, using tetraethoxysilane as precursor. The thermal stability and micromorphology of the reinforced silica aerogel and composite silica aerogel had been studied by the differential thermal analysis, thermogravimetric analysis and scanning electron microscopy and these properties had been compared with pure silica aerogel. The results showed that the weight loss of silica aerogels increased a little and the thermal stability decreased slightly after fiber and TiO2 power were doped. But the porous netted structure of obtained reinforced and composite silica aerogels were very even and ordered, which will be enough to satisfy the demands of the super heat insulation and heat preservation of materials in the fields of avigation, spaceflight, civilian technology and industry.